Antimicrobial resistance genes and class 1 integrons in MDR Salmonella strains isolated from swine lymph nodes - Possebon, Fábio Sossai [UNESP]; Alvarez, Marcus Vinicius Niz [UNESP]; Ullmann, Leila Sabrina [UNESP]; Araújo Jr, João Pessoa [UNESP] (Elsevier, 2021)
Food safety is essential to the development of a society, and foodborne diseases affect thousands of people worldwide every year. Among the main foodborne disease agents, Salmonella stands out as the most often associated with hospitalizations and deaths. Pork products are an important source of nutrients for the population, considered the most consumed meat in the world. Several reports revealed the presence of Multidrug-Resistant (MDR) Salmonella strains along the pork production chain, and the occurrence of elements that allow for the transference of resistance genes between bacterial populations is a public health concern. The present work aimed to evaluate the resistance genes and integrons in MDR Salmonella strains isolated from swine mesenteric lymph nodes. Nine strains had the genome sequenced with the Illumina NextSeq system. The results were submitted to the Resfinder server for evaluation of acquired genes and point mutations related to AMR and the presence and sequences of integrons were determined with a BLAST search. Different resistance genes for the same antimicrobial class were present in each strain. In two samples, resistance genes for olaquindox, a growth promoter outlawed in Brazil since 2004, were found. All observed phenotypic resistance had a genetic basis. Five isolates harbored class 1 integrons, which were classified in three distinct Integron Profiles (IPs). The IPs were also reported in animal source food and human clinical isolates. The diversity of resistance genes for the same antimicrobial class in each strain and the presence of Class 1 Integrons, reflect the high selection pressure that these bacterial lineages face along the pork production chain, and reinforces the role of animal production as a reservoir and disseminator of AMR genes.
Keywords: Integrons; MDR; Resistance profile; Salmonella; WGS